Examining the Issue of Native-Speakerism in English Language Teaching in Indonesian Context - Rina Febrina Sarie (Jurnal Bahasa dan Sastra, 2018)
Abstract: Native-speakerism is defined as an ideology which brings the idea that so-called ‘native speakers’ are trusted as the best models and teachers of English. In the context of English as a Foreign Language (EFL) particularly in Indonesian setting, the practitioners of English Language Teaching (ELT) often show favouritism towards Native English Speaker Teachers (NESTs) and do marginalize the Non-Native English Speaker Teachers (NNESTs). This phenomenon affects their equality of opportunity and impacts on different right they will have. Realising this bigger impact, experts and scholars in ELT raise their voice to eliminate the native speaker fallacy. Therefore, this paper attempts to contribute to the discussion by examining critically the unfairness between NESTs and NNESTs in teaching English in EFL contexts particularly in Indonesia, and eventually proposing the pedagogy of English as an International Language (EIL) to encounter this native-speakerism issue. Keywords: native-speakerism, native and non-native English speaker teachers, English as an international language (EIL) Abstrak: “Native-speakerisme” didefinisikan sebagai ideologi yang membawa ide bahwa 'penutur asli' dipercaya sebagai model dan guru bahasa Inggris terbaik. Dalam konteks bahasa Inggris sebagai Bahasa Asing (EFL) khususnya di konteks Indonesia, para praktisi Pengajaran Bahasa Inggris (ELT) sering menunjukkan favoritisme terhadap Guru Penutur Asli Bahasa Inggris (NEST) dan memarginalkan Guru Penutur Non-Asli Bahasa Inggris (NNEST). Fenomena ini mempengaruhi kesetaraan kesempatan dan dampaknya pad hak yang berbeda yang akan mereka dapatkan. Menyadari dampak yang lebih besar ini, para ahli bidang ELT angkat suara untuk mengatasi kekeliruan penutur asli. Oleh karena itu, makalah ini berupaya merangkum pandangan-pandangan yang kritis terkait diskusi isu ketidak adila antara Guru Penutur Asli Bahasa Inggris (NEST) dan Guru Penutur Non-Asli Bahasa Inggris (NNEST) dalam mengajar bahasa Inggris di konteks Indonesia, dan akhirnya mengusulkan sebuah pedagogi yakni Bahasa Inggris sebagai Bahasa Internasional (EIL) untuk menghadapi masalah “native-speakerisme” ini Kata-kata kunci: native-speakerism, native and non-native english speaker teachers, English as an international language (EIL)